Gagasan Yuridis Gratifikasi Seksual Sebagai Bentuk Tindak Pidana Korupsi Di Indonesia - Rahayu, Ayda; Artina, Dessy; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Corruption is an enemy of every country in the world, and we all know that money is the mainsource of corruption. Lubis and Scott in their view of corruption say: "in the legal sense, corruption isbehavior that benefits self-interest by harming others by government officials who directly violate legalboundaries over such behavior, whereas according to government norms can be considered corruption ifthe law is violated or not in the business the action is despicable ". This criminal offense not only harmsstate finances, but also violates the social and economic rights of the community.This research is sociological or empirical research, namely the type of research that usescommunity assumptions in looking for facts that occur in the field to answer an existing problem. Thisresearch was carried out in the Riau High Prosecutor's jurisdiction. While the population and sample areparties related to the problems examined in this study, the data sources used, primary data, secondary data,and tertiary data. The technique of collecting data in this study was through interviews and literaturereview.From the results of the research the authors did can be concluded, firstThe role of the Riau High Prosecutor's Intelligence in the disclosure of alleged criminal acts ofcorruption is to conduct judicial intelligence activities and operations or investigations to collect data orinformation that can be used as evidence about whether or not a corruption has occurred which is thensubmitted to the Chairperson or party have an interest in further decision making. The obstacles faced byRiau High Prosecutor Intelligence in uncovering alleged corruption in the Riau High Prosecutor's lawregion, namely human resource (HR) factors, the factors of legislation that were felt to be incompatible withthe demands of community development, the difficulty factor for the Prosecutor Intelligence in obtainevidence in the form of letters, valuable documents, and related assets, factors in the lack of fundsallocation, factors in lack of coordination by the Prosecutor's Intelligence with related agencies, and factorsin the lack of planning carried out by Riau Prosecutor's Intelligence Office.Keywords: Juridical Ideas - Sexual Gratification - Corruption Crime.